2018
DOI: 10.1177/1073110518782916
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Incentives for Novel Inpatient Antibiotics: No One-Size-Fits-All

Abstract: The need for new "pull" incentives to stimulate antibiotic R&D is widely recognized. Due to the global diversity of health systems, combined with different challenges faced by antibiotics used in different types of healthcare settings, there is no one-size-fits-all solution. Instead, different "pull" incentives should be tailored to local contexts, priorities, and antibiotic types. Policymakers and industry should collaborate to identify appropriate solutions at the local, regional, and global levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Some bacteria are intrinsically resistant to certain antimicrobials through functional or structural characteristics (e.g., absence of target) (Blair et al, 2015). Alternatively, AMR can be acquired or developed through spontaneous mutation, horizontal gene transfer, and genetic recombination, all of which can provide a competitive advantage (Laxminarayan et al, 2013;Blair et al, 2015;Chan, 2016). Recent studies have identified a large number of genes responsible for intrinsic and/or acquired AMR in microorganisms (van Hoek et al, 2011;Blair et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria are intrinsically resistant to certain antimicrobials through functional or structural characteristics (e.g., absence of target) (Blair et al, 2015). Alternatively, AMR can be acquired or developed through spontaneous mutation, horizontal gene transfer, and genetic recombination, all of which can provide a competitive advantage (Laxminarayan et al, 2013;Blair et al, 2015;Chan, 2016). Recent studies have identified a large number of genes responsible for intrinsic and/or acquired AMR in microorganisms (van Hoek et al, 2011;Blair et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance has steadily increased in clinical settings (Bitnun and Yeh, 2018). We are on the cusp of returning to a pre-antibiotic world in which common infections and minor injuries will once again become deadly (Laxminarayan et al, 2013; Ferri et al, 2017; Pawar et al, 2017). Simultaneously, natural product discovery efforts on the part of the pharmaceutical industry have largely dwindled since the end of the 20th century (Baker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, antibiotics in a US hospital setting are funded through diagnosis-related groups (DRGs), which classify admissions based on principal diagnosis. Under this system, hospitals are reimbursed at a predetermined rate for healthcare services and drug costs according to the assigned DRG [20]. Often in a hospital setting, prices rather than the broader benefits or cost offsets of therapies are emphasized during selections of drugs to include in a formulary [20].…”
Section: Introductionmentioning
confidence: 99%
“…Under this system, hospitals are reimbursed at a predetermined rate for healthcare services and drug costs according to the assigned DRG [20]. Often in a hospital setting, prices rather than the broader benefits or cost offsets of therapies are emphasized during selections of drugs to include in a formulary [20]. Therefore, bundling the cost of an antibiotic into a DRG payment can discourage the use of high-cost therapies such as fidaxomicin because of hospital budget constraints.…”
Section: Introductionmentioning
confidence: 99%